PEMUTAKHIRAN PETA PENGGUNAAN DAN PEMANFAATAN TANAH KOTA YOGYAKARTA (Studi Kasus : Kota Yogyakarta, Daerah Istimewa Yogyakarta) - , RIZKY ERLANGGA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The development of Yogyakarta is growing rapidly due to economics and social factors are increasing too. That development is status alteration of land use and utilization in Yogyakarta, for example rice field becomes housing. Considering the land resource has geospatial dimension, presenting information in land thematic map form is needed to have better understanding about land problems. The updating of Land Use and Land Utilization Map was started by collecting all of the datas (land use map 2010, Ikonos image of Yogyakarta 2011, and the result of land use and utilization survey). This applicative activity was implemented in Yogyakarta by using overlay technique between land use map and Ikonos image map Yogyakarta, while the analysis was done by comparing the visual interpretation of the image and the result of survey. The result of this applicative activity Land Use Map and Land Utilization Map of Yogyakarta is in 1 : 15.000 scale. These thematic maps are updated for land administration purposes in Yogyakarta. It is also used for controlling the development of land use and land utilization in Yogyakarta, because in fact there are too many people using and utilizating lands only for economics puposes.